All for one and one for all: heterogeneity of genetic etiologies in neurodevelopmental psychiatric disorders. (June 2021) - Moreno-De-Luca, Daniel; Martin, Christa Lese
Abstract : Alexandre Dumas' famous phrase All for One and One for All recapitulates our current understanding of the genomic architecture of neurodevelopmental psychiatric disorders (NPD), like autism Spectrum disorder, bipolar disorder, and schizophrenia. Many rare genomic variants of large effect size have been identified; a ll of them together can explain a significant proportion of NPD. In parallel, one rare genomic variant can cause all of the above NPD. Finally, common genomic variants of individually small effect size can be combined to further explain risk for NPD. How do we reconcile different genomic variants accounting for one clinical diagnosis, and different clinical diagnoses arising from a single genomic variant? Here, we discuss a framework to understand genetic and clinical heterogeneity in NPD.